1993
DOI: 10.1002/jmv.1890400204
|View full text |Cite
|
Sign up to set email alerts
|

Improved detection of rhinoviruses in nasal and throat swabs by seminested RT‐PCR

Abstract: A seminested RT-PCR (nRT-PCR) was used to detect picornavirus (PV) RNA in cell cultures inoculated with rhinoviruses (HRVs) and enteroviruses (EVs). PCR tests in which a primary "touchdown" PCR was followed by secondary reactions using PV or HRV specific primers were able to differentiate HRVs of 48 serotypes from EVs. PVnRT-PCR and HRVnRT-PCR were then used to test nasal and throat swabs from adult subjects with naturally acquired respiratory virus infections. The swabs were also analysed for respiratory viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 21 publications
(13 reference statements)
2
90
0
Order By: Relevance
“…Although other studies have shown that respiratory virus infections may lead to exacerbations in patients with chronic chest disease [1][2][3][4][5][6][7][8][9][10] recently been described and evaluated in our laboratory [26]. RT The results of this study illustrate the morbidity and undoubted economic importance of respiratory virus infections.…”
Section: Discussionmentioning
confidence: 75%
“…Although other studies have shown that respiratory virus infections may lead to exacerbations in patients with chronic chest disease [1][2][3][4][5][6][7][8][9][10] recently been described and evaluated in our laboratory [26]. RT The results of this study illustrate the morbidity and undoubted economic importance of respiratory virus infections.…”
Section: Discussionmentioning
confidence: 75%
“…Serological diagnosis of rhinovirus is hampered by the large number of serotypes (>100) and limited cross-reactivity [22]. Recently, it has been found that detection of rhinovirus could be improved by up to five times using PCR [14,23]. Thus, using PCR, rhinovirus has been shown to be the predominant virus, associated with 50% of asthmatic exacerbations in children and 33% in adults and 19% of exacerbations of cystic fibrosis, with smaller proportions of exacerbations attributed to other viruses [6,18,24].…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory syncytial virus, adenovirus, influenza A and B, and parainfluenza types 1, 2, or 3 were either detected by 1) direct fluorescent Ab testing with virus-specific mAbs (Meridian Bioscience and Dako) or 2) isolation in cell culture (cell lines include LLC-MK, A549, Hep-2, Vero, and MRC-5) and identification with the virus-specific monoclonal antisera, 48 h after inoculation. Human rhinovirus (19,20) and coronavirus 229E and OC43 (21) were detected by previously described RT-PCRs, and human metapneumovirus detection utilized in-house primers designed to target nuc and matrix genes. For aspirates with sufficient sample remaining for retesting (the majority), respiratory viruses were detected by Respiratory MultiCode-PLx assay (22) and human rhinovirus was identified with a molecular typing assay (23).…”
Section: Subjects and Clinical Assessmentsmentioning
confidence: 99%